Constellations - Kim, F. S (New York Children's Press, 2010)
An illustrated introduction to constellations that explains how constellations are useful, who discovered them, and related topics
The stars in our sky -- The view from earth -- A history of constellations -- Star stories -- Constellations around the world
Includes bibliographical references (p. 44-45) and index
Hurg
5 8
Keywords: Constellations -- Juvenile literature; Constellations